Job satisfaction among primary school teachers in Samarahan / Aennie Nursyuhada Kadir and Normaizan Zambri - Kadir, Aennie Nursyuhada; Zambri, Normaizan (2011)
Teacher plays an important role in achieving the objectives of Malaysian Vision in order to produce the innovative and progressive society. According to Bishay (1996), the teaching profession ranks high on the success list of a society. Job satisfaction amongst teachers is a multifaceted construct that is critical to teacher retention and has been shown‘to be a significant determinant of teacher commitment, and in turn, a contributor to school effectiveness. Moreover, they have also been linked to increase productivity and organizational effectiveness (Buitendach and De Witte, 2005). Research, however, reveals wide ranging differences in what contributes to job satisfaction and group differences according to demographic factors (Shan, 1998). Evans (1998) mentions that factors such as teachers' low salaries and low status growing class sizes and changes in the education system have all contributed as cause of dissatisfaction within the profession. From research undertaken by Duke (1988), there is a worldwide tendency towards job dissatisfaction in education. However, Steyn and Van Wyk (1999) contend that contrary to expectations, teachers experience greater work satisfaction than was previously believed. Therefore, research in job satisfaction can help the organization to identify the main factor or dimension which affect job satisfaction among the school teachers. From the study, the organization can make adjustments on their current policies and procedures as an effort to increase the level of job satisfaction and improve the school teachers’ commitment on their profession.